Molecular identification of sex in date palm using PCR: a study from Gujarat, India - Mansi Jani; Haidar Abbas Masi; Chaitanya Joshi; Fenil Patel; Madhvi Joshi (Journal of Genetic Engineering and Biotechnology)
The date palm (Phoenix dactylifera L.) is a dioecious plant species characterised by separate male and female sex organs on distinct plants. Accurate sex determination of date palm seedlings holds paramount importance in augmenting fruit production by selecting female plants. However, conventional techniques for sex differentiation are labour-intensive and necessitate several years. In this investigation, a sex determination approach for date palm using Polymerase Chain Reaction (PCR), employing a male-specific primer targeting Glycerol-3 Phosphate Acetyltransferase (GPAT3), as the marker for male identification along with LOX5.1 as a positive control to validate the amplification process. GPAT3 is acknowledged for its pivotal role in male fertility. Our work reveals that GPAT3 amplification exclusively transpired in male date palm samples, whereas female samples exhibited no amplification of GPAT3. Consequently, the presence of two distinct PCR bands signifies a male plant, whereas a single band designates a female plant. To ascertain the effectiveness of these primers, 280 date palm samples obtained from various regions of Gujarat, India and successfully ascertained the sex of each specimen. This PCR-based sex determination method provides a swift and dependable means of early-stage sex identification in date palms in Gujarat, thereby facilitating enhanced date palm cultivation practices and heightened fruit production.